Keanekaragaman Jenis Gastropoda di Desa Ampibabo Timur Kecamatan Ampibabo Kabupaten Parigi Moutong dan Pemanfaatannya Sebagai Sumber Belajar - Diaz Pratama; Fatma Dhafir; Ritman; Bustamin (Universitas Tadulako, 2021)
One of the marine biota found in Ampibabo Village Beach is Gastropods. The objectives of this research are; (1) determine the Diversity of Gastropod Species in Ampibabo Timur Village, Ampibabo Subdistrict, Parigi Moutong Regency, (2) use research results as a learning resource in the form of a pocket book. The type of research used is descriptive qualitative and quantitative research. The object of this research is the types of gastropods. The sample data collection method used a survey method with the help of line transects, data analysis was carried out by calculating the diversity index using the Shannon-Winner formula. The results showed that: (1) there were 15 types of gastropods with a total of 258 individuals. The most common species found was Nassarius pullus, which was 47 individuals from all research stations. While Conus marmoreus is the least found gastropod species, as many as 3 individuals/species, the Gastropod Species Diversity Index in Ampibabo Timur Village, Ampibabo District, Parigi Mouotng Regency in general is 1.07 or H' is moderate, (2) the results of the assessment of pocket book products which was obtained from lecturers of content experts, namely 77.1%, design experts 74.6%, and media experts, namely 84%, then from student trials of 20 respondents, the average value was 80.5%. With these criteria, this pocket book on the diversity of gastropod species is feasible to use.